1055. Assessing the Impact of the Routine Childhood Hepatitis B Immunization and the Need for Hepatitis B Vaccine Birth Dose in Sierra Leone, 2018. (31st December 2020) - Breakwell, Lucy; Marke, Dennis; Kaiser, Reinhard; Tejada-Strop, Alexandra; Pauly, Matthew; Stewart, Brock; Kabore, Hyacinte J; Sesay, Tom; Samba, Thomas; Hayden, Tonya; Kamili, Saleem; Jambai, Amara; et al.
Abstract: Background: All African countries recommend 3 doses of hepatitis B vaccine (HepB3), most at 6, 10, and 14 weeks of age, but few recommend a HepB birth dose (HepB-BD). To evaluate the role of mother to child transmission (MTCT) of hepatitis B virus (HBV) with the 3 dose HepB schedule, we conducted a serosurvey in Sierra Leone among 4–30 month old children and their mothers, and 5–9 year old children. Methods: We conducted a multi-stage cluster survey in 3 districts. Enumeration areas (EA) were selected by probability proportional to size, followed by random selection of eligible households to identify 1901 children per age group. We tested all participants for HBV surface antigen (HBsAg) by rapid test and collected children's HepB vaccination history. Serum from all HBsAg+ mothers and 1 HBsAg- mother per EA was tested for total antibodies to HBV core antigen (anti-HBc), HBsAg, HBV e antigen (HBeAg), and HBV DNA. We assessed the association of HBsAg prevalence with HepB vaccination and maternal HBV markers. Results: Among 1889 children aged 4–30 months, 20 (1.3%; 95% CI:0.8%–2.0%) were HBsAg+; HepB3 coverage was 85%. Among 2025 children aged 5–9 years, 32 (1.6%; 95% CI:1.1%–2.3%) were HBsAg+; HepB3 coverage was 77%. Of HBsAg+ children, 70% (14/20) of younger and 56% (18/32) of older children received HepB3. Among 1776 mothers of younger children, 169 (9.8%; 95% CI:8.1%–11.7%) were HBsAg+. HBsAg prevalence for children with HBsAg+ mothers was 5.9% (10/169) and 0.7% (6/1605) for those with HBsAg- mothers (adjusted OR=10.6 [95% CI:2.8–40.8]). Of 139 HBsAg+ mothers, 13 (9%) were HBeAg+ and 126 (91%) had detectable HBV DNA. Maternal HBsAg (p=0.026), HBeAg (p< 0.001), and HBV DNA levels ≥ 200, 000 IU/mL (p< 0.001) were associated with HBsAg positivity in younger children (Table 1). Table 1: Association of maternal HBV serological and molecular markers with HBsAg positivity in 4–30-month old children — Sierra Leone hepatitis B serosurvey, 2018 Conclusion: HBsAg prevalence was much lower among children than among mothers, for whom HepB would not have been available, indicating that routine infant HepB vaccination has substantially lowered HBV burden. Increasing HepB3 coverage could further reduce HBsAg prevalence among children. As HBsAg positivity in young children was strongly associated with having a mother with active HBV infection and > 50% of HBsAg+ children received HepB3, HepB-BD is needed to prevent MTCT of HBV and chronic HBV infections in children. Disclosures: All Authors : No reported disclosures